The Quality of Life of a Multidiagnosis Group of Special Needs Children: Associations and Costs - Sandy Thurston; Louise Paul; Patricia Loney; Maria Wong; Gina Browne (Hindawi Limited, 2010)
Purpose. To determine the quality of life, associations, and costs of a multidiagnosis group of special needs children. Methods. In this cross-sectional survey families were identified from the Children's Treatment Network, a Canadian multisector program for children with special needs. Families were eligible if the child was aged 2-19 years, resided in Simcoe/York, and if there were multiple child/family needs. Quality of life was measured using the PedsQL (n=429). Results. Quality of life scores were lower in this group compared to published healthy and single disorder groups of children. Quality of life scores decreased with advancing age. Child psychosocial well-being was more strongly associated with child/family variables compared to physical well-being. Health Utilization costs were higher in children with greater physical challenges. Conclusions. Further research is needed in other complex needs child samples to confirm the decrease in quality of life found in these children into adolescence. Investigations into the interactions of child and family variables are needed.